Effect of perioperative acupuncture-assisted general anesthesia on the anesthetic dosage required in adult surgical patients: a network meta-analysis of randomized controlled trials - Qiu, Meihua; Li, Chuanxiong; Sun, Tong; Ruan, Qianwen (Frontiers in Medicine, 2023)
Objective: To determine the comparative effects of acupuncture and related techniques-assisted general anesthesia (GA) on the total dosage of main anesthetic drugs administered during surgery. Methods: The following data bases were searched on June 30, 2022: Embase, Cochrane, PubMed, Web of Science, CBM, CNKI, WANFANG and VIP to find randomized controlled trials (RCTs). A random-effects Bayesian network meta-analysis and subgroup analysis were employed. The GRADE system was applied to make evidence quality assessments. The intraoperative total doses of propofol and remifentanil were the primary and secondary outcomes, respectively. The weighted mean difference (WMD) with 95% confidence intervals (CI) were determined to measure the size of any potential effect. Results: Seventy-six RCTs that involved 5,877 patients were included in the analysis. Compared with GA, a significant decrease in the total dose of propofol was found for manual acupuncture (MA) assisted GA (WMD = -101.26 mg, 95% CI [-172.98, -27.06]) with moderate quality, electroacupuncture (EA) assisted GA (WMD = -54.25 mg, 95% CI [-87.25, -22.37]) with moderate quality and transcutaneous electrical acupoint stimulation (TEAS) assisted GA (WMD = -39.99 mg, 95% CI [-57.96, -22.73]) with moderate quality, respectively. A significant reduction in the total dose of remifentanil was found in favor of EA-assisted GA (WMD = -372.33 μg, 95% CI [-558.44, -196.43]) with low quality and TEAS-assisted GA (WMD = -215.77 μg, 95% CI [-305.23, -128.04]) with low quality. According to the surface under cumulative ranking area (SUCRA), MA-assisted GA and EA-assisted GA ranked first in the reduction of the total dosage of propofol and remifentanil administered, with a probability of 0.85 and 0.87, respectively. Conclusions: Both EA- and TEAS-assisted GA significantly reduced the intraoperative total dosage of propofol and remifentanil administered. EA produced the greatest reduction in these two outcomes compared to TEAS. Although all the comparisons are low to moderate based on GRADE evidence, EA seems to be an advisable acupuncture technique to reduce the dosage of anesthetic drugs required in surgical patients under GA.